Some Methods of Teaching English via Online Learning System Used by Lecturers; A Descriptive Study - Juliansyah Juliansyah (ITScience (Information Technology and Science), 2021)
Firstly, the research aims to know what lecturers use methods of teaching English via an Online Learning System. Secondly, the activities both the lecturers and students have during the learning process. This research is limited to what methods the lecturers apply in teaching English for English department students via an online learning system to build students' enthusiasm for learning. The process of research used is qualitative research. In collecting data, the researcher used observation. There are 8 respondents in this research. They are all lecturers teaching in English Department. The result shows that the lecturers use applications in teaching English, namely Google Classroom, Google Meet, Zoom, and the Learning Management System (LMS) of Darma Persada University, namely portal.unsada.ac.id. The latest application is an official site that lecturers and students use to proceed with the teaching-learning process. The research also finds that lecturers do several activities in the learning process. They fill in the blank, read aloud, answer questions, picture describing, drilling, and presentation techniques. The research shows that those all activities are the most suitable with learning system using online. Meanwhile, in terms of teaching techniques, most of the lecturers use communicative language teaching, grammar-translation, and audio-lingual method.